Investigation of Maximum Mid-Span Displacement and Reaction Forces in Fiber-reinforced Concrete Beams subjected to Impact - Mahmoud, Zena; Aldosary, Muhannad; Al-Hadithi , Abdulkader Ismail (Engineering, Technology & Applied Science Research, 2024)
Self-Compacting Fiber-Reinforced Concrete (SCFRC) is a specialized type of concrete that combines the properties of Self-Compacting Concrete (SCC) with the addition of fibers for reinforcement. SCFRC is designed to have excellent flowability and self-leveling characteristics while providing enhanced tensile strength, ductility, and crack resistance. This paper presents a discussion on the topic of SCFRC and the impact load behavior of SCFRC beams reinforced with Waste Plastic Fibers (WPFs). A comparison with reinforced concrete beams without fibers is also conducted. This study aims to predict the maximum mid-span displacement and the maximum reaction force of the fiber concrete beams under impact load. Twelve beams that represent the total adopted parameters were tested under impact loading. The beams were divided into three main groups according to the longitudinal steel ratio. The steel ratio was varied by using steel bars of 10, 8, and 6 mm diameter, with PET waste fibers with different volume ratios Vf% of 0, 0.5, 0.75, and 1%. The results showed that the use of beams is reinforced with ρmax, ρmax< ρ< ρmin, and ρmin having reduced maximum deflection by 24.23%, 35.9%, and 46.28%, respectively, when using WPFs with a volumetric value of 1%. This paper also covers work steps, model details, and the tests that were carried out on the specimens, which were made from materials available in local markets.